Сто великих полководцев Второй мировой - Лубченков Юрий Николаевич (Сто великих, 2006)
Экземпляры: ф.12 (2008) / Инвентарный номер: 52213 / Цена: / Сис.шифр: 63.3(0)62 / Авт.знак: Л 82 / ГРНТИ: 03.23.55 / ББК: 63.3(0)62-8